(untitled) (SCIÉNDO INGENIUM, 2021)
The purpose of the investigation was to demonstrate that Criminal Compliance in construction companies, has as philosophical support, the validity of the norm and social control, as well as socio-legal support, is justified in the trust of the companies’ self-regulatory system, to achieve exemption from criminal responsibility. To achieve the objectives, it began with the observation of standard cases (cassation in criminal matters), then it was contrasted with the current regulation, and in the discussion the interpretation provided by the specialized doctrine of recent date was used. The problem statement was formulated as follows: What is the philosophical, socio-legal basis of Criminal Compliance in construction companies, as a self-regulatory model for the prevention of money laundering acts in Peru? Finally, the contribution of this investigation consisted in providing theoretical and practical support for criminal compliance, while its affirmation as a self-regulatory system, capable of preventing risks of money laundering acts, within the business organization depends on it.